COFFEE BEANS DRYING USING THE ELECTRICAL ENERGY OF MICRO-HYDRO POWER PLANT AT ANDUNGBIRU, TIRIS, PROBOLINGGO - mega nur sasongko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
Coffee bean dryer is one of the solutions to solve the problems in the village of Andungbiru, Tiris, Probolinggo. The drier can be used to minimize the power loss in micro hydro power plant and increase the production of coffee without depending on the weather and sunshine. This coffee dryer was designed to have a compact and mobile. It consisted of 20 vertical drying rack arranged to save the energy. Using the drier, time and human energy used for drying coffee became shorter and more efficient. The cost was five times more cheaply compared to drying in a conventional manner. Besides, the application of coffee dryer was also be used for drying grain because it was equipped with temperature control to regulate the temperature inside the oven. The use of this coffee dryer had other benefits for management micro-hydro power plant. Electrical energy from micro hydro plant which usually discarded during the day, could be used for the processing of coffee